The influence of brand authenticity and open communication on social media on brand trust and brand loyalty: a case study of UINSU students in the era of digital marketing - Tia Nava Utari Tanjung; Imsar Imsar; Faisal Umardani Hasibuan (Institute of Accounting Research and Novation (IARN), 2026)
This study aims to analyze the influence of brand authenticity and communication openness on social media on brand trust, as well as its implications for brand loyalty among students at the State Islamic University of North Sumatra (UINSU). The background of this study is based on the growing use of social media as a primary tool in digital marketing activities, which serves not only as a promotional medium but also as a space for interaction between brands and consumers. The research approach used was quantitative, with data collected through a questionnaire distributed to UINSU students who actively use social media. The data obtained were then analyzed using SPSS to test the relationships between variables. The results show that brand authenticity and open communication on social media have a positive and significant effect on brand trust. Furthermore, brand trust was found to have a positive and significant effect on brand loyalty. These findings indicate that honesty, brand consistency, and open and responsive communication are important factors in building consumer trust, which ultimately fosters brand loyalty